Silvicultural Attempts to Induce Browse Resistance in Conifer Seedlings - Bruce A. Kimball; Fred Pfund; Mark Gourley; Doreen L. Griffin; John H. Russell (International Journal of Forestry Research)
A multiyear study was conducted to determine if soil amendment combined with topical application of elemental sulfur could be employed to reduce deer browse damage to four conifer species. Fertilizer and sulfur were applied to conifer seedlings at seven sites near Corvallis, OR. Growth and browse damage data were collected for all seedlings over a period of 17 months. Additionally, foliar concentrations of monoterpenes and simple carbohydrates were assessed in western redcedar (Thuja plicata) seedlings over a period of three years. Fertilization and sulfur treatments had a moderate impact on growth and no influence on browse damage or the chemical responses. Over the course of the study, browse damage diminished while foliar monoterpene concentrations increased in redcedar. It appears that silvicultural manipulation via sulfur application and/or soil amendment cannot accelerate or alter the ontogenetical changes that may naturally defend seedlings against mammalian herbivores. In a brief trial with captive deer, redcedar browse resistance was influenced by seedling maturation, but not monoterpene content. Other maturation effects may yield significant browse protection to young seedlings.